2011
DOI: 10.1007/s00264-011-1249-z
|View full text |Cite
|
Sign up to set email alerts
|

Balloon reduction and cement fixation in intra-articular calcaneal fractures: a percutaneous approach to intra-articular calcaneal fractures

Abstract: Purpose The management of calcaneal fractures remains challenging and often controversial. Open reduction and internal fixation with a lateral plate has been established as a standard therapy for displaced articular fractures. However, accurate subtalar joint reduction, while mandatory, is difficult to achieve, requires an extensive lateral approach, and clinical results may not be up to the difficulty of the task. Methods We present a treatment using a percutaneous approach and local balloon reduction followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…height, width and length, should be restored to provide the best possible walking capacities. So, alternative procedures have been proposed, including two-stage procedures [5,6], minimally invasive techniques [7][8][9][10], balloon reduction and cement fixation [11,12] and even a tailormade treatment strategy [13]. Indeed, most minimally invasive techniques achieve reduced primary stability and reduction accuracy is difficult to verify even with arthroscopy or 3D fluoroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…height, width and length, should be restored to provide the best possible walking capacities. So, alternative procedures have been proposed, including two-stage procedures [5,6], minimally invasive techniques [7][8][9][10], balloon reduction and cement fixation [11,12] and even a tailormade treatment strategy [13]. Indeed, most minimally invasive techniques achieve reduced primary stability and reduction accuracy is difficult to verify even with arthroscopy or 3D fluoroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the paper by Jacquot et al [1]. The authors concluded that a percutaneous approach and local balloon reduction followed by polymethylmethacrylate (PMMA) fixation may be promising and may be used in cases with closed fractures as a primary reduction and fixation tool.…”
Section: Dear Editormentioning
confidence: 75%
“…For comminuted fractures (Sanders type III and type IV), the posterior articular fractured into more than two fragments, and it was difficult to reduce all fragments into contact with their subtalar counterparts using a balloon only, especially the central fragment. Case 2 of Jacquot's patients was a Sanders IIIBC fracture; the central fragment was not reduced anatomically and a step was present [1]. Perhaps the short-term outcome was not influenced but it does suggest a limitation of this technique.…”
Section: Dear Editormentioning
confidence: 99%
“…All cases were operated on in the prone position with a double image intensifier control in the lateral and AP/ thalamic view as already described [5][6][7]. Additional reduction techniques were used, such as lateral compression using two plastic slabs and a large reduction clamp, as well as "framing" of the fracture using temporary plantar K-wire stabilisation to direct the pressure of the balloon towards the thalamic fragment.…”
Section: Techniquementioning
confidence: 99%
“…The technique has been described in several papers recently with technical details [2][3][4][5][6][7][8]. However, it lacks follow up and clinical evidence of efficacy.…”
Section: Introductionmentioning
confidence: 99%